Terrorist attacks: cutaneous patterns of gunshot and secondary blast injuries - Yann Delannoy; Isabelle Plu; Isabelle Sec; Tania Delabarde; Marc Taccoen; Antoine Tracqui; Bertrand Ludes (Oxford University Press, 2020)
Terrorist attacks have been on the rise. During the recent terrorist attacks in France, terrorists perpetrated their acts using weapons of war, as well as explosive charges. These two modes of action, when combined, can create skin lesions with similar macroscopic appearances, which can sometimes go unnoticed because of body fragmentation. A total of 68 autopsies, 83 external examinations, 140 standard radiographic examinations, and 49 computed tomography (CT) scans were performed over 7 days during the 2015 terrorist attacks in France. Bodies were injured by firearms and shrapnel-like projectiles. We analysed the clinical findings for the secondary blast cutaneous lesions from the explosive devices and compared these lesions with ballistic-related lesions to highlight that patterns can be macroscopically similar on external examination. Secondary blast injuries are characterised by penetrating trauma associated with materials added to explosive systems that are propelled by explosive air movement. These injuries are caused most often by small, shrapnel-like metallic objects, such as nails and bolts. Propulsion causes ballistic-type injuries that must be recognised and distinguished from those caused by firearm projectiles. Differentiating between these lesions is very difficult when using conventional criteria (size, shape, number and distribution on the body) with only external examination of corpses. This is why the particularities of these lesions must be further illustrated and then confirmed by complete autopsies and radiological and anatomopathological examinations.Key points When occurring simultaneously in terrorist attacks, injuries caused by secondary blasts appear as cutaneous wound patterns that can be macroscopically very similar to those caused by firearm projectiles. The criteria usually found in the literature for distinguishing these two types of projectiles may be difficult to use. It is important in these difficult situations to benefit from systematic postmortem imaging. Systematic autopsy and then anatomopathological analyses of the orifices also help determine the cause of the wounds.